2011
DOI: 10.1007/s12010-011-9278-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases and Hemicellulases from Endophytic Acremonium Species and Its Application on Sugarcane Bagasse Hydrolysis

Abstract: The aim of this work was to have cellulase activity and hemicellulase activity screenings of endophyte Acremonium species (Acremonium zeae EA0802 and Acremonium sp. EA0810). Both fungi were cultivated in submerged culture (SC) containing L -arabinose, D -xylose, oat spelt xylan, sugarcane bagasse, or corn straw as carbon source. In solid-state fermentation, it was tested as carbon source sugarcane bagasse or corn straw. The highest FPase, endoglucanase, and xylanase activities were produced by Acremonium sp. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 56 publications
3
17
0
1
Order By: Relevance
“…An initial screening under different SSF conditions indicated that the highest enzyme activities of endoxylanase, β-xylosidase, endoglucanase, cellobiohydrolase I and β-glucosidase for both S4F8 and Rut C30 were recorded after 3 days of incubation on SCB (data not shown) as opposed to the 7 days typically reported for fungal SCB SSF [10,42]. …”
Section: Resultsmentioning
confidence: 99%
“…An initial screening under different SSF conditions indicated that the highest enzyme activities of endoxylanase, β-xylosidase, endoglucanase, cellobiohydrolase I and β-glucosidase for both S4F8 and Rut C30 were recorded after 3 days of incubation on SCB (data not shown) as opposed to the 7 days typically reported for fungal SCB SSF [10,42]. …”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, the interest in cellulases and hemicellulases has increased due to the ethanol production from lignocellulosic residues (de Almeida et al 2011). Xylanases have been extensively studied for their usage in the production of hydrolysate from agro-industrial wastes, in nutritional improvements of lignocellulosic feeds, processing of food, in increasing animal feed digestibility, biobleaching of paper pulp, clarification of fruit juices and wine, the extraction of plant oil, coffee and starch (Ahmed et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…As regards molds, there are very few studies of Sarocladium strains in literature. De Almeida et al (De Almeida et al 2011) described two strains of Sarocladium able to produce Filter Paper-cellulase, endo-1,4-β-D-glucanase, endo-1,4-β-Dxylanase, β-glucosidase, α-arabinofuranosidase and α-galactosidase. In another study, a strain of Sarocladium fuci was found to produce α-amylase, lipase, protease and cellulase but no β-glucosidase (Zuccaro et al 2004).…”
Section: Isolates and Enzyme Productionmentioning
confidence: 99%